Dynamic capability of P-solubilizing endophytic and rhizospheric bacteria from various vegetation of Alas Bromo for reducing chemical fertilizer use - Prasgi, Henokh Christian; Ariyanto, Dwi Priyo; Cahyani, Vita Ratri (Journal of Degraded and Mining Lands Management, 2025)
The application of agrochemicals is still the main practice in the agroforestry system of Alas Bromo. Alfisols in Alas Bromo were characterized as acidic soil with very low soil available P. This study aimed to examine the capacity of P-solubilizing endophytic and rhizospheric bacteria from various Alas Bromo vegetation: mahogany, wresah, peanut, elephant grass, and maize in increasing soil available P and enhancing maize growth, which has the potential for reducing chemical fertilizer use. The research began with exploring and isolating bacteria using Pikovskaya agar medium, followed by in vitro tests of functional abilities and greenhouse experiments (soil incubation continued with maize planting). Rock phosphate was used as a P-inorganic source with a dose of 150 kg   ha-1. Based on the highest PSI, a total of 15 out of 52 isolated bacteria from 5 vegetations were selected to be tested in vitro and in a greenhouse experiment. Among the assessed bacteria, 3 endophytic bacterial isolates of Ad_R_5, Ah_R_4, and Zm_L_6 showed consistently high performance during successive assessments. Compared to basal treatment, the increases of soil available P, shoot fresh weight, and shoot dry weight by these 3 superior isolates ranged from 51.11-90.29%, 38.27-89.75%, and 57.04-88.73%, while the increases by NPK were 93.53, 113.67 and 107.04%, indicating the isolates had high potential for reducing chemical fertilizer use. The 3 superior isolates were identified as Pantoea dispersa, Ralstonia picketii, and Enterobacter hormaechei, respectively. Further study is needed to investigate the other potential capabilities, such as pesticide degradation and supporting plant resistance to drought stress.